Pragmatic and Grammatical Competence Interface in Second Language Acquisition: Conceptual Framework and Construction - Rustandi, Andi; Febriani, R. Bunga; Sugiarto, Bambang Ruby (JALL (Journal of Applied Linguistics and Literacy), 2025)
This study investigated the interface between pragmatic and grammatical competence in second language acquisition. This study aims to discover the conceptual framework of how pragmatics competence interfaces with grammatical competence. This study employs three research questions such as (1) how pragmatics competence and grammatical competence are interfaced with each other, (2) what kind of pragmatics competence should be learned by the learner of a second language, and (3) to what extent grammatical construction interface with the pragmatic domain. This study used the groundwork of the library research method, which forms the theoretical framework of this study by searching, reading, and evaluating some journals from the online journal that deals with the topic. The result revealed that pragmatic competence and grammatical competence are interfaced with each other since grammatical construction in the utterance contributes to the language use expression.